Consumption of energy-dense, nutrient-poor foods and hypertension in obese children - Mohammad Sulchan (Indonesian Pediatric Society, 2014)
Background Obesity has become an increasingly important medicalproblem in children. Obesity-induced hypertension in childhoodshould be considered as a chronic medical condition that is likelyto require long-term management of dietary patterns, especially forenergy-dense, nutrient-poor (EDNP) food consumption.Objective To examine the contribution ofEDNP foods to dailyenergy and macronutrient intakes and to examine the relationshipbetween intake of EDN P foods and the prevalence of hypertensionin children.Methods Four hundred and forty children were randomly selectedto participate. Weight and height were measured with precisionelectronic scales and fixed microtoise, respectively. Blood pressure(BP) measurements were performed by standard procedure. A24-hour dietary recall was obtained by a trained interviewer todetermine the intake of EDNP foods, which were clas sified to 4major groups: visible fat, sweeteners, desserts, or salty snacks.The difference in mean was evaluated using paired Ttest.Logistic models were fitted to assess for an association betweenhypertension and the various characteristics.Results The proportion of children who were overweight (includingobese) was 23 .2%. The prevalence of elevated BP was 10.5%, similarin boys and girls, with most of them having isolated elevated sys to lieBP. There was a relationship between BP and body mass index(BMI) in all children. Approximately 27% of total daily energyintake was contributed by all EDNP foods. Of the EDNP foodsubgroups examined, dessert and sweeteners contributed nearly20% of total daily energy intake. In the highest one-third of subjectswho consumed EDNP food, these foods provided 49% of total dailycarbohydrate intake and 34% of total daily fat intake.Conclusion Eating patterns ofEDNP foods provide 49% of totaldaily carbohydrate intake and 34% of total daily fat intake. ThisEDNP food is independently associated with hypertension inchildren.